Meningkatkan Belajar Secara Kritis Materi Makna Paham Gereja Dengan Metode PBL Fase F di Kelas XI SMK Negeri 1 Raya - Eva Petro Sinaga (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
This research is classroom action research (ptk) which consists of 2 cycles and 4 stages of planning, implementation, observation and reflection collecting pretest scores, cycle 1, cycle II. The subjects in this research were all 10 class XI students. In the initial conditions, the evaluation results of students who studied completely only reached 5 students (27.78%), while in the first cycle, there were 10 students who were able to study completely (55.56%). The criteria for complete learning are based on the grades achieved that have reached or exceeded the KKM (minimum completion criteria), namely ≥ 75 for Catholic religion and character subjects. In the second cycle, there were 10 students who were able to study completely (88.89%). The criteria for complete learning were based on the grades achieved by students who had reached or exceeded the KKM (Minimum Completeness Criteria) at SMK NEGERI 1 RAYA for the 2019/2020 Academic Year. In summary, it can be concluded that the results of the second cycle from the aspect of participation and collaboration in groups in the learning process have been achieved at 88.89%. This achievement has exceeded the set success indicators, namely 86%